Enhancement of immune response induced by DNA vaccine cocktail expressing complete LACK and TSA genes against Leishmania major. Issue 4 (18th September 2012) - Ghaffarifar, Fatemeh; Jorjani, Ogholniaz; Sharifi, Zohreh; Dalimi, Abdolhossein; Hassan, Zuhair M.; Tabatabaie, Fatemeh; Khoshzaban, Fariba; Hezarjaribi, Hajar Ziaei
<x xml:space="preserve">Abstract</x> Leishmaniasis is an important disease in humans. Leishmania homologue of receptor for Activated C Kinase (LACK) and thiol specific antioxidant (TSA) as immuno‐dominant antigens of Leishmania major are considered the most promising molecules for a DNA vaccine. We constructed a DNA cocktail, containing plasmids encoding LACK and TSA genes of Leishmania major and evaluated the immune response and survival rate in BALB/c mice. IgG and Interferon gamma values were noticeably increased in the immunized group with DNA cocktail vaccine, which were significantly higher than those in the single‐gene vaccinated and control groups (p < 0.05) following the immunization and after challenging with Leishmania major. Interleukin 4 values were decreased in all immunized groups, but only in DNA vaccine cocktail and single‐gene vaccination with pc‐LACK there were statistical differences with control groups (p > 0.05). The immunized mice with the cocktail DNA vaccine presented a considerable reduction in diameter of lesion compared to other groups and a significant difference was observed (p < 0.05) in this regard. The survival time of the immunized mice with the cocktail DNA vaccine was significantly higher than that in the other groups (p < 0.05) after their being challenged with Leishmania major. The findings of this study indicated that the cocktail DNA vaccine increased the cellular response and survival rate and induced protection against infection with Leishmania in the mice.